Nursing students’ perceptions of spiritual needs at the end of life. A qualitative study - García-Navarro, E. Begoña; Navarro, Sonia García; Sousa, Luis; José, Helena; Caceres-Titos, María José; Ortega-Galán, Ángela (Frontiers in Psychiatry, 2023)
Spirituality is defined as the meaning of life, being the very essence of life made up of all of the aspects inherent to it. During end-of-life processes, this need is shown to be particularly altered in patients and yet it is an aspect that the health professionals accompanying patients in this situation report being least equipped to address, alongside therapies that could help to meet these needs, such as art therapy. An exploratory qualitative study was conducted, adheres to the guidelines of COREQ (41). The study population were final year students undertaking a nursing degree at the University of Huelva, Spain. The sample was selected via intentional sampling using snowball recruitment from the study population. Stratification according to gender was performed due to the feminised nature of the population. Sample size was determined progressively during the research, with recruitment ceasing at 13 informants once information saturation was achieved. Inclusion criteria required that participants were to be final year students enrolled on a nursing degree who had provided consent to participate voluntarily in the research. The analysis Realized was interpretive phenomenological (IPA) as described by Smith (43–45). The present study revealed that students perceive their training on spiritual care to be deficient. Despite them reporting that they possess the skills and tools to provide end-of-life care, this is not enough to provide effective accompaniment, given that this moment brings them into touch with their own insecurities. Students verbalized the need to learn strategies to address this shortcoming regarding final accompaniment, for instance, through art, with creativity being one of the skills with the potential to uncover the meaning of life.